(untitled) (Research, Society and Development, 2022)
In a world that is increasingly dominated by computers and their digital systems, computer accessibility resources play their full role in achieving the objective of assistive technologies. The present study aimed to present the DOSVOX program as an assistive technology that helps the process of school inclusion of blind students with visual impairment, through a mini course in distance learning that sought to guide teachers about the use of this Assistive technology. The methodology used was an exploratory, qualitative field research and was guided by three main points: the importance of using computer accessibility resources in the classroom; the lack of knowledge of these resources by most teachers; and the need to spread the use of Assistive Technologies. A to promote inclusive environments. The research approach followed the participatory model, employing semi-structured interviews for data collection. Regarding the results obtained, we could see that the knowledge of education professionals about AT is low. In this way, a change in attitude and a search for knowledge that promotes accessibility is relevant, aiming to effectively contribute to the educational development of students with visual impairments.